Caution in interpretation of abnormal carbon monoxide diffusion capacity in COVID-19 patients. Issue 1 (28th January 2021) - Chapman, David G.; Badal, Tanya; King, Gregory G.; Thamrin, Cindy
We read with much interest the recent findings published in the European Respiratory Journal of reduced gas transfer in patients following coronavirus disease 2019 (COVID-19). Mo et al. [1] investigated conventional pulmonary function in survivors of mild, moderate and severe COVID-19 approximately 20–30 days after onset of symptoms. While patients had relatively normal spirometry, diffusing capacity of the lung for carbon monoxide ( D LCO ) was reduced in 50% and D LCO /alveolar volume ( V A ) (or K CO, to avoid misinterpretation) reduced in 25%. These findings are welcome as they provide significant insight into the long-term lung function impairment associated with COVID-19. Reduced K CO in discharged patients with COVID-19 suggests persistent abnormalities in gas exchange. Further research is required to understand why. https://bit.ly/2Hb00gq